Right and Left: Dissent in the debate on university quotas in Carta Capital and Veja magazines (Intercom - Brazilian Journal of Communication Sciences, 2024)
The aim of this study was to identify and understand the social representations of university quotas published in Carta Capital and Veja Brazilian magazines between 2008 and 2017. A total of 199 texts were analyzed, which showed that ideological bias acted as a metasystem to promote dissent in the understanding of the object under investigation. In comparison, Carta Capital’s social representations were based on the notion of fairness and social equality, while Veja’s texts approached university quotas as a partisan, unfair and non-meritocratic measure. The research was exploratory-descriptive in nature and used analysis supported by the Iramuteq software and the societal approach of the Theory of Social Representations.
Keywords: niversity quotas. Ideology. Carta Capital. Veja. Social representations